The Role of Information and Communication Technology in Islamic Education: Challenges and Opportunities - Shafira Fatimah Azzahra; Lubis, Muharman (Yayasan Asmin Intelektual Berkah, 2024)
In this paper, the role of information and communication technology (ICT) in Islamic education is analyzed with an emphasis on the challenges and opportunities it presents. ICT can increase access to Islamic knowledge, improve teaching methods, and encourage participatory learning. It is necessary to handle issues including restricted infrastructure, the requirement to maintain high-quality Islamic material online, and cultural and religious sensitivity in online learning settings. ICT presents several opportunities for Islamic education, including the use of multimedia and interactive tools for teaching Islamic concepts, facilitating global reach and accessibility through online platforms, and fostering collaboration and knowledge-sharing among educators and scholars. To evaluate the effect of ICT on Islamic education, qualitative research using content analysis was carried out. The results draw attention to issues including the limitations of ICT infrastructure, the need for high-quality online information, the necessity of good ICT training for teachers, and cultural and religious considerations. ICT also offers chances for improved Quranic study, worldwide cooperation, ongoing learning outside of the classroom, and expanded access to Islamic information. In order to use ICT to enhance Islamic education, this study intends to provide useful insights for educational practitioners and policymakers.